Pengaruh Knowledge Management, Digital Marketing, Dan Inovasi Terhadap Kinerja Usaha Kecil Di Kota Makassar - Rukaiyah, St; Laan, Rahmat; Bangaran, Yoel Limbu (Jurnal Online Manajemen ELPEI, 2025)
This research aims to investigate whether there is a positive influence of knowledge management, digital marketing, and innovation on the performance of small businesses in the city of Makassar. In this study, a quantitative approach is used, and the sampling method employed is the Slovin formula with the criteria of small business operators in the city of Makassar. The data collection technique is by distributing questionnaires directly and in the form of a Google Form. There are 88 respondents who are the sample in this study. This research uses descriptive statistical analysis testing with the SPSS version 26 application. The results of this study indicate that knowledge management has a significant impact on the performance of small businesses in the city of Makassar, digital marketing has a significant impact on the performance of small businesses in the city of Makassar, and innovation has a significant impact on the performance of small businesses in the city of Makassar.